ChemInform Abstract: Zinc‐Catalyzed Dual C—X and C—H Borylation of Aryl Halides. Issue 5 (January 2016) - Bose, Shubhankar Kumar; Deissenberger, Andrea; Eichhorn, Antonius; Steel, Patrick G.; Lin, Zhenyang; Marder, Todd B.
Abstract: A combined C—halogen and ortho C—H borylation process is developed using aryl iodides and bromides and (Bpin)2 as the boron source.